Defining the benchmark research sites (rural to urban transect) in Vietnam - Haan, Stef de; Huynh, Tuyen; Duong, Thanh Thi; Rubin, Julia (2020)
A multi-stakeholder survey and site-based data comparison was carried out to predefine three benchmark sites or populations along a rural-to-urban transect. The current report is a draft version to be shared widely with A4NH- FSHD partners before we commit to ACTUALLY initiating food system characterization in each site, followed by different types of action research based on a clear and concerted rationale, during the upcoming 5 year period of phase II of A4NH-FSHD.